Analyzing Trends and Framework Models for Autonomous Vehicle Transition Strategies - Cintia Nurliyana; Yuliani Dwi Lestari; Eko Agus Prasetio; Prawira Fajarindra Belgiawan (Journal of the Civil Engineering Forum, 2026)
The shift from traditional human-driven to autonomous vehicles represents a transformation that is not merely technological, but also social. Currently, the deployment of autonomous vehicles remains largely at level where the human driver continues to be the primary decisionmaker. However, this dynamic is expected to change significantly as higher levels of autonomy are achieved. This study aims to identify the impacts that occur during process transition through emerging trends and theoretical lens of transition studies. The initial stage involved mapping trends in Autonomous Vehicle (AV) research to identify key related topics. This study uses bibliometric analysis of 82 key articles selected through a screening process in a systematic review. VOSviewer and CiteSpace were employed to map the research landscape, identify dominant topics, and trace the evolution of AV studies over time. The analysis highlights both well-established research areas and underexplored gaps. Furthermore, the articles were classified into categories based on transition study dimensions and key actors involedinvolved in facilitating a successful transition. The findings reveal a dominant research focus on users, human factors, and mobility behavior, whereas studies concerning vulnerable road users and the industry transition remain limited. To address this gap, this study investigates the socio-technical factors arising from the identified trends and transition studies while also exploring the roles of key stakeholders. This approach aims to achieve a more balanced perspective. Specifically, the study proposes a novel framework that connects critical actors with core socio-technical dimensions to support a sustainable autonomous ve-hicle transition. This research thus provides a strategic framework designed to guide and accelerate the shift toward autonomous mobility.